If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + (x + -2) + (2x + -1) = 18 Reorder the terms: 3x + (-2 + x) + (2x + -1) = 18 Remove parenthesis around (-2 + x) 3x + -2 + x + (2x + -1) = 18 Reorder the terms: 3x + -2 + x + (-1 + 2x) = 18 Remove parenthesis around (-1 + 2x) 3x + -2 + x + -1 + 2x = 18 Reorder the terms: -2 + -1 + 3x + x + 2x = 18 Combine like terms: -2 + -1 = -3 -3 + 3x + x + 2x = 18 Combine like terms: 3x + x = 4x -3 + 4x + 2x = 18 Combine like terms: 4x + 2x = 6x -3 + 6x = 18 Solving -3 + 6x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 6x = 18 + 3 Combine like terms: -3 + 3 = 0 0 + 6x = 18 + 3 6x = 18 + 3 Combine like terms: 18 + 3 = 21 6x = 21 Divide each side by '6'. x = 3.5 Simplifying x = 3.5
| 1-5x+6x^2=0 | | 5-3x-2x^2=0 | | -5y+6=-4(2y+3) | | x+3=2x^2 | | y=8-12+2y | | 5x+20x=1320 | | 5x-20x=1320 | | -(a-5)+7=-(8+3a) | | -4(1+2n)=-2(n-1) | | 90=10(x+16) | | x+(x-2)= | | 17x=-12 | | 5(v-7)=-39+3v | | 6(x+1)=-5x-5 | | 35=10b+50 | | 2x+4(2x+7)=3(2x+4) | | -(3+2x)=17 | | 4b^2=9 | | 6-(-6b-3)=-3b-27 | | -32-5x=2(4x-6)-7 | | a-0.66667a=8 | | -3(2z-5)=-2z-3z+21 | | 6-x=8-2x | | (X-5)1.5=8 | | a-0.75a=6 | | x(x-12)=-35 | | 6+0.75a=a | | 2(x-6)-6(x-2)=x+5-(x-11) | | -2x+13=10-2x | | -9=x+(-19) | | 7y-2=19y+82 | | 10x-(6x-5)=41 |